The interactive correlation between the multidimensional motivation of athletic practice and the motive of athletic achievement among Algerian professional and unprofessional athletes. - OUNANE , Saidi (sports creativity, 2025)
This study revolves around the interactive correlation between the elements of the multi- dimensional motivation of sports practice (internal motivation and external motivation and after a lack of motivation) on the one hand and the motivation of athletic achievement on the other hand among the Algerian athletes of high level. The relational descriptive approach was relied on a sample consisting of 213 athletes, of whom 121 are unprofessional and 92 professionals, and it is a stratified random sample. For data collection, the Sports Motivation Scale EMS 28 of Billard N. Valero and his colleagues was used and the sports achievement motivation scale for Jules Arabization Mohammed Hassan Allawi, Results were reached confirming the existence of a correlation between the multi-dimensional motivation and the motivation of the relatively sporty achievement among the sample